Corporate communication : a guide to theory and practice - Cornelissen, Joep, ....- (Thousand Oaks (Cal.) : SAGE Publications Ltd., 2014)
Praise for the Previous Edition: 'This book guides newcomers as well as skilled students within the field of corporate communication through the subject with great vigour, enthusiasm as well as clarity. The book works very well as textbook for my course' - Anna Karina Kjeldsen, Aarhus University 'An excellent book for our course Managing Corporate Communication. Builds on solid theory but is practically oriented; a very good combination for Master's students in communication in a Business School environment' - Leena Louhiala-Salminen, Aalto University School of Economics New to the Fourth Edition: * Discussion of the new media environment for corporate communication * Expansion to include new up-to-date material such as emerging CSR standards, transnational governance and corporate citizenship * Enhanced companion website material with new video clips, case studies and SAGE online readings. Essential reading for students studying Corporate Communication, Organizational Communication, PR and Marketing Communications.
Keywords: Communicatie -- Organisaties; Corporate communication